2017
DOI: 10.1002/jso.24589
|View full text |Cite
|
Sign up to set email alerts
|

CT‐guided percutaneous hookwire localization increases the efficacy and safety of VATS for pulmonary nodules

Abstract: CT-PHL is a very efficient and safe procedure prior to VATS for pulmonary nodules and allows in 96% radical resection with a diagnostic accuracy of 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 36 publications
(106 reference statements)
2
45
2
Order By: Relevance
“…Surgeons palpated the scar with the help of probe or finger and resected corresponding parenchyma in VATS procedure. In most cases, localization time was less than 20 minutes, similar to other localization studies (11).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Surgeons palpated the scar with the help of probe or finger and resected corresponding parenchyma in VATS procedure. In most cases, localization time was less than 20 minutes, similar to other localization studies (11).…”
Section: Discussionsupporting
confidence: 88%
“…All nodules were successfully localized without major complications. The conversion rate of VATS to thoracotomy was lower than other studies (11). In our study, minor hemorrhage, indicated by small areas of consolidation in the lung window on final CT scan, was found in 3 patients, with no cases of hemoptysis.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…With the widespread use of low‐dose CT screening, the detection rate of lung nodules is increasing . Thoracoscopic wedge resection is considered the best choice for the diagnosis of lung nodules . In addition, wedge resection can be used as a radical treatment for adenocarcinoma in situ (AIS) and microinvasive adenocarcinoma (MIA) …”
Section: Introductionmentioning
confidence: 99%
“…reported one case (0.7%) and Chen et al . two cases (4.9%) of dislodgement in their studies; thus, open thoracotomy was performed as an alternative . Dislodgement could have occurred during transport to surgery, during positioning of the patient on the operating table, during deflation of the non‐ventilated lung, or as a result of the surgeon's manipulation during VATS .…”
Section: Discussionmentioning
confidence: 99%